2016
DOI: 10.1183/13993003.00823-2016
|View full text |Cite
|
Sign up to set email alerts
|

Desipramine improves upper airway collapsibility and reduces OSA severity in patients with minimal muscle compensation

Abstract: We recently demonstrated that desipramine reduces the sleep-related loss of upper airway dilator muscle activity and reduces pharyngeal collapsibility in healthy humans without obstructive sleep apnoea (OSA). The aim of the present physiological study was to determine the effects of desipramine on upper airway collapsibility and apnoea–hypopnea index (AHI) in OSA patients. A placebo-controlled, double-blind, randomised crossover trial in 14 OSA patients was performed. Participants received treatment or placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 38 publications
(46 reference statements)
1
61
0
Order By: Relevance
“…As the role of non-anatomical factors becomes more important than upper airway anatomy, one or more interventions for each physiological impairment can be chosen in order to target treatment to improve upper airway muscle function, i.e. upper airway muscle stimulation [75,76], drugs [77], reduction of loop gain using acetazolamide [78] or increase of the arousal threshold using hypnotics [79][80][81][82][83]. While interested readers are referred to extensive reviews on this topic [42,84,85], some critical points need to be highlighted.…”
Section: Arousal Thresholdmentioning
confidence: 99%
“…As the role of non-anatomical factors becomes more important than upper airway anatomy, one or more interventions for each physiological impairment can be chosen in order to target treatment to improve upper airway muscle function, i.e. upper airway muscle stimulation [75,76], drugs [77], reduction of loop gain using acetazolamide [78] or increase of the arousal threshold using hypnotics [79][80][81][82][83]. While interested readers are referred to extensive reviews on this topic [42,84,85], some critical points need to be highlighted.…”
Section: Arousal Thresholdmentioning
confidence: 99%
“…Epiglottic pressure was determined with a small, flexible pressure‐tipped catheter (Millar Instruments, Houston, TX, USA) as described previously (Taranto‐Montemurro et al . )…”
Section: Methodsmentioning
confidence: 99%
“…This approach is necessary for this review because previous attempts at OSA pharmacotherapy have largely been ineffective (for reviews see 3338 ) and in many ways this has been predictable based on the targets chosen, and because the trials were comprised of un-phenotyped OSA patients, only a subset of which would be expected to benefit even if the pharmacological target was rational and effectively manipulated (discussed in Section 3.2). More recent clinical studies, however, using agents targeting the significant mechanisms of state-dependent pharyngeal muscle control identified from basic science experiments 3942 , have proved beneficial when administered to phenotyped patients 43, 44 , with other studies ongoing 45–47 .…”
Section: Strategic Directions From the Phenotype Model And Identifmentioning
confidence: 99%
“…Nevertheless, the number and selectivity of drugs associated with a given target is useful information, not least because it can be taken as an indicator of the relative druggability of that target. Moreover, initial studies have shown that desipramine has beneficial effects on genioglossus muscle tone, upper airway collapsibility and OSA severity 43, 44 . Desipramine is a tricyclic anti-depressant with strong noradrenergic and some anti-muscarinic effects.…”
Section: Mapping Potential Drug Targets In the Circuitry Controllimentioning
confidence: 99%